2008
DOI: 10.1017/s0007114508043377
|View full text |Cite
|
Sign up to set email alerts
|

Niacin for dairy cattle: a review

Abstract: Due to the incorporation of niacin into the coenzymes NAD and NADP, niacin is of great importance for the metabolism of man and animals. Apart from niacin in feed and endogenous formation, microbial niacin synthesis in the rumen is an important source for dairy cows. But the amount synthesised seems to differ greatly, which might be influenced by the ration fed. Many studies revealed a positive impact of a niacin supplementation on rumen protozoa, but microbial protein synthesis or volatile fatty acid producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 53 publications
(206 reference statements)
4
57
3
Order By: Relevance
“…In addition, taking cows and heifers together, the animals were in a less pronounced negative energy balance, so no effect was found on milk yield or FCM yield. This is in agreement with Niehoff et al (2009a), who concluded that the absence of a niacin effect could be explained because the cows were too far into lactation, and thus not in a negative energy balance , as in the present trial when cows and heifers were evaluated together. If they were considered separately, it could be seen that the cows had entered a negative balance (Figure 7), owing to their higher milk performance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, taking cows and heifers together, the animals were in a less pronounced negative energy balance, so no effect was found on milk yield or FCM yield. This is in agreement with Niehoff et al (2009a), who concluded that the absence of a niacin effect could be explained because the cows were too far into lactation, and thus not in a negative energy balance , as in the present trial when cows and heifers were evaluated together. If they were considered separately, it could be seen that the cows had entered a negative balance (Figure 7), owing to their higher milk performance.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study niacin had no effect on milk fat content. In most studies reviewed by Niehoff et al (2009a), no effect was found for milk fat yield or milk protein content or yield. Differing from this, Belibasakis & Tsirgogianni (1996) found increased fat concentration and yield due to niacin (10 g/d); Erickson et al (1992) found milk protein concentration increased (12 g NA/d); while Drackley et al (1998) found it decreased (12 g/d).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Animal requirements for some nutrients may be much higher than previous estimates based upon concentrations in their diets and microbial biomass (Santschi et al, 2005). As most supplemental AA and water soluble vitamins have been shown to be extensively degraded in the rumen (Niehoff et al, 2009;Zimbelman et al, 2010), dietary supplementation without rumen protection is a very inefficient nutrient delivery mechanism to the intestinal absorptive site.…”
Section: Introductionmentioning
confidence: 97%